Parasitization preference of Diaeretiella rapae (Hymenoptera: Braconidae) among different aphids in vegetable ecosystem - HALDER, JAYDEEP; RAI, A B; KODANDARAM, M H (The Indian Journal of Agricultural Sciences, 2014)
Solitary, polyphagous, endoparasitoid Diaeretiella rapae (Mc’Intosh) is considered as one of the prominent parasitoid of aphids on several host plants under natural field conditions. However, knowledge about its affinity and host preference towards different prey aphids is very scanty. So the present study on host preference of D. rapae revealed differential response for its parasitization to different aphid species infesting vegetable crops. It preferred maximum to cruciferous aphids, viz. Myzus persicae (59%) followed by Brevicoryne brassicae (51%) and Lipaphis erysimi (46%) than the other vegetable aphids like Aphis craccivora (23.67%) and Aphis spiraecola (19.67%). Seasonal incidence of D. rapae also indicated that its first occurrence was observed on M. persicae (13.67%) and L. erysimi (5.67%) during second fortnight of January, 2013 whereas spiraecola feeding on brinjal parasitized last indicating the preference of cruciferous aphids over other vegetable aphids. However, among the cruciferous aphids, highest parasitoid emergence was observed from L. erysimi (88%) followed by B. brassicae (81%) and M. persicae (80%). Comparatively higher body size (2.81 ± 0.23 mm) and tibial length (0.51 ± 0.05 mm) of M. persicae by the parasitoid for its parasitization and variation in nutritional quality in L. erysimi as food substrate towards D. rapae for its higher emergence might be responsible for their preference over the other host aphids.